PELATIHAN EFEKTIFITAS OPERASIONALISASI PEMBERKASAN SURAT BAGI PEGAWAI DI KANTOR KEPALA DESA CITERAS KEC. RANGKASBITUNG KAB. LEBAK – BANTEN - Rosali Sembiring; Nurhafifah Matondang (LPPM UPN Veteran Jakarta, 2021)
Each company must manage the administration of existing letters in the company / office effectively so that it does not interfere with company operations. Procedures are a series of tasks that are integrated in an integrated manner with one another.Citeras village office employees have an important role in serving the administrative needs of the Citeras village community for writing correspondence to and from various institutions, the general public and organizations. Many letters are made and received by village office employees that require structuring, filing and filing letters / documents so that they can be neatly and well organized.The method of implementing this community partnership program activity is the method of participation, namely collaboration between the service team and Citeras village officials. This method is used so that partners can apply it at the village office after training on filing of letter / document archives at the village office so that administration at the village office is neatly organized and there is no difficulty finding the required incoming or outgoing mail archives.Assistance to village office employees is carried out so that the skills of village office employees can increase, this can be seen from the results of the questionnaire and the neat and good administration of the village office. It is hoped that a good administrative arrangement can be maintained so that the community can be served as expected by the government, namely providing the best for the community.